Endotoxemia and cardiometabolic biomarkers in patients with acute myocardial infarction. Data from the RICO survey. (14th October 2021) - Putot, A; Masson, D; Cottin, Y; Gauthier, T; Tribouillard, L; Rerole, A L; Maza, M; Pais De Barros, J P; Deckert, V; Farnier, M; Lagrost, L; Zeller, M; et al.
Abstract: Background: The complex interplay between endotoxemia, inflammation and cardiometabolic diseases including acute myocardial infarction is poorly understood. Aim: Our prospective study aimed to address the determinants of endotoxemia, including blood lipids and metabolic biomarkers, in patients admitted for an acute MI. Methods: From the RICO survey, patients admitted to the coronary care unit of our University Hospital for type 1 acute MI were prospectively included between 2016 and 2018. Patients with prior coronary artery disease (CAD) or chronic kidney disease were excluded. Blood samples for biomarkers measurement were taken on admission. Endotoxemia was assessed by the LCMSMS measurement of circulating levels of LPS-derived 3-hydroxymyristate (3HM), a component of the lipid A moiety. Results: Among the 245 patients included, mean age was 62±13 y, most were male (72%), almost half were hypertensive (43%), or current smokers (44%), 38% had hypercholesterolemia, or family history of CAD (31%), median (IQR) BMI was 27 (25–29) kg/m 2 and 14% had diabetes. Median LDL-cholesterol was at 132 mg/dL, HDL-cholesterol at 47 mg/dL, total cholesterol at 209 mg/dL and triglycerides (TG) at 116 mg/dL. Median (IQR) 3HM levels were at 106 (83–131) pmol/L. Among biomarkers, TG levels were the most strongly correlated with LPS levels (r=0.201, p=0.002), beyond HbA1c (r=0.197, p=0.002), BMI (r=0.192, p=0.003), cholesterol (r=0.191, p=0.003), blood glucose (r=0.174, p=0.006) and age (r=0.173, p=0.007). Inflammatory biomarkers and cytokines (CRP, IL6, IL8, TNF α) did not significantly relate to 3HM levels. When compared with patients without diabetes, patients with diabetes had ≈40% higher levels of 3HM (140 vs 103 pmol/L, p<0.001). By multivariate regression linear analysis, TG (β(95% CI)=0.288 (7.757–20.357), p<0.001) remained an independent determinant of 3HM levels, beyond age (β(95% CI)=0.184 (0.274–1.374), p=0.003), and HbA1c (β(95% CI)=0.157 (1.764–15.390), p=0.014). Conclusions: In a former analysis of our prospective study in patients with acute MI, endotoxemia levels related mainly to chronic metabolic disorders including diabetes and hypercholesterolemia. The underlying mechanisms for the LPS-associated TG elevations and its clinical significance at the acute phase of MI remains to be explored. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): CHU Dijon Bourgogne ARS Bourgogne Franche comté